Criminal Responsibility of Criminals Defamation on Advocate Name - Bambang Lasimin Arek; Umar Ma'ruf (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
The purpose of this research is to know and understand the legal responsibility of the criminal defamation against lawyers according to Islamic criminal law, to know and understand the legal responsibility of the criminal defamation against lawyers according to Indonesian criminal law as well as to know, understand and analyze the legal accountability of the perpetrators criminal defamation against advocates at the Law Supremacy & Associate law office in Police Report Number: LP / B / 115B / XI / 2019 / Jabar according to Islamic criminal law and Indonesian criminal law. The approach method used in this research is normative juridical. The research specification used in this research is descriptive analytical. The theory used in analyzing the above problems is the rule of law theory, the theory of legal certainty and the theory of criminal responsibility in Islamic law. The conclusion of this study is that legal responsibility for the perpetrators of criminal defamation against advocates according to Islamic law is a Ta’zir sentence in the form of a limited prison sentence, where the length of the sentence is handed over to Ulil Amri who examines the case, while according to Indonesian criminal law it is a prison sentence and fines. Legal accountability for perpetrators of criminal defamation against advocates in the Police Report Number: LP / B / 115B / XI / 2019 / Jabar, according to Islamic law, is punishable by Ta’zir in the form of limited prison. Meanwhile, according to Indonesian criminal law, the actions of suspects are subject to imprisonment and a fine, in accordance with the provisions of Article 311 paragraph (1) and Article 315 of the Criminal Code.